Peningkatan Kemampuan Problem Solving Siswa SMP Al-Ikhlas dengan Metode Mind Mapping dan Pohon Masalah - Zuraida, Dita Juwita; Sulis, Ken Heryani; Asih, Marlia Tyas; Raharjo, Toto (The IMPACT : Jurnal Pengabdian Kepada Masyarakat Universitas Islam As-Syafiiyah, 2025)
The purpose of this program was to enhance the problem-solving skills of 8th-grade students at SMP Al-Ikhlas, Jakarta, who often face difficulties in applying learned concepts to real-life situations. This community service activity was conducted on August 19, 2024, involving 150 students. The methods used were Mind Mapping and Problem Trees, chosen as visualization tools to help students systematically and creatively identify problems, analyze root causes, and formulate solutions. The implementation stages included material explanation, a Q&A session, hands-on practice with relevant case studies, and evaluation through group presentations. The evaluation results showed a significant improvement, with 78.4% of participants reporting that they felt capable of solving problems independently after participating in the activity. Nevertheless, continued guidance from school counselors is still considered important. This program proved effective in equipping students with essential foundational skills to face future challenges.